Structural Aspects of Shariah-Compliant, Women-Friendly Mosques: Towards a Generalizable Design Framework (Lembaga Contrarius Indonesia, 2026)
Mosques function as vital spaces for sustained worship and community engagement; however, structural provisions for women’s religious and communal activities are often inadequately addressed or insufficiently aligned with Shariah requirements. This inadequacy constitutes a core problem, as non-compliant or poorly designed architectural features may hinder women’s participation and compromise adherence to Islamic legal principles. Accordingly, this study addresses the problem by systematically examining structural design aspects and synthesizing them into a generalizable framework for Shariah-compliant, women-friendly mosque design. This article analyzes mosque design features that fulfill Shariah requirements for women, particularly regarding the preservation of modesty and privacy, ʿawrah, and the practical needs of women’s religious activities. Methodologically, the study adopts a qualitative approach comprising document analysis and observation, complemented by semi-structured interviews with relevant stakeholders from mosque institutions. The findings indicate that improving mosque design toward outcomes that are women-friendly and Shariah-compliant requires the development of dedicated guidelines specifying spaces for worship and women’s religious and community activities, thereby aligning mosque environments with Shariah obligations for women.